Kirindi Oya Irrigation Settlement Project: project impact evaluation study. Vol.1: Main report (final) - International Irrigation Management Institute (International Irrigation Management Institute, 1995)
The KOISP Project Impact Evaluation Study was a collaborative research effort between the International Irrigation Management Institute (IIMI) and the Agrarian Research and Institute (ARTI) with the former having the overall responsibility. The two institutes shared responsibility of hiring and fielding the research team. Consultants Ruhunu University have also been engaged by IIMI through a research contract. The broad objective of the project was to attempt to assess the overall effects of the interventions as implemented under the KOISP. More specifically, the objectives of the were to i) identify and measure KOISP outputs and trends; (ii) to measure the benefits and evaluate the impacts of the project and (iii) to conduct a cost-benefit of the KOISP.